2020
DOI: 10.1038/s41598-020-69842-x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of adolescent girls and young women for targeted HIV prevention: a new risk scoring tool in KwaZulu Natal, South Africa

Abstract: The ongoing spread of human immunodeficiency virus (HIV) has driven novel interventions, such as antiretrovirals, for pre-exposure prophylaxis. Interventions have overlooked a high-risk Sub-Saharan African population: adolescent girls and young women (AGYW), particularly those under 18. We apply the Balkus risk tool among rural South African AGYW (n = 971) in a hyper-endemic setting, identify limitations, and assess deficiencies with modern statistical techniques. We apply the “Ayton” tool, the first risk tool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…The majority (10 of 13) were among women only, of which three were restricted to young women under age 25 or lower; three included women and men aged 15–49 years or 15 years and older. The majority (10 of 13) were RCTs or quasi‐experimental studies that restricted recruitment and/or eligibility to specific at‐risk population groups: (1) sexually active, contraception‐seeking women who attended the family‐planning, STIs or research clinics (7 of 10, all RCTs) [ 8 , 9 , 24 , 25 , 26 , 27 , 28 ], or (2) school‐attending AGYW (3 of 10) [ 29 , 30 , 31 ]. The remaining three were large‐scale cohort studies or community trials that recruited all consenting members within the communities [ 32 , 33 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…The majority (10 of 13) were among women only, of which three were restricted to young women under age 25 or lower; three included women and men aged 15–49 years or 15 years and older. The majority (10 of 13) were RCTs or quasi‐experimental studies that restricted recruitment and/or eligibility to specific at‐risk population groups: (1) sexually active, contraception‐seeking women who attended the family‐planning, STIs or research clinics (7 of 10, all RCTs) [ 8 , 9 , 24 , 25 , 26 , 27 , 28 ], or (2) school‐attending AGYW (3 of 10) [ 29 , 30 , 31 ]. The remaining three were large‐scale cohort studies or community trials that recruited all consenting members within the communities [ 32 , 33 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…One additional conference abstract was available after initial screening, adding to a total of 13 risk score literature (9 peer-reviewed articles, 2 posters, 1 editorial letter, 1 abstract) that met the inclusion criteria and were included in this review (Figure 1) [5,6,[20][21][22][23][24][25][26][27][28][29][30]. Critical appraisal according to the PROBAST checklist concluded that one out of twelve models developed and two out of nine validated were of low risk of bias (Figure S1, Table S3 & S4).…”
Section: Resultsmentioning
confidence: 99%
“…The majority (10 of 13) were RCTs or quasi-experimental studies that restricted recruitment and/or eligibility to specific at-risk population groups: (i) sexually active, contraceptionseeking women who attended the family-planning, STIs or research clinics (7 of 10, all RCTs) [5,6,[20][21][22][23][24], or (ii) school-attending AGYW (3 of 10) [25][26][27]. The remaining three were large-scale cohort studies or community trials that recruited all consenting members within the communities [28][29][30].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Identifying who to reach with which interventions remains a challenge. Studies exist examining the determinants of adolescent sexual and reproductive health [ 6 , 7 , 8 ], conceptual models [ 9 ], and research approaches [ 10 ] that aim to better understand vulnerability to HIV among AGYW as well as the recent development of prognostic risk tools [ 11 , 12 ]. Organizations supporting countries to customize and target their interventions, so that they reach those AGYW most in need, recommend [ 13 , 14 ] programmers to assess the factors that make AGYW vulnerable and exacerbate their risk of acquiring HIV/STIs or unintended pregnancy.…”
Section: Introductionmentioning
confidence: 99%